Housing provisions and affordability in private residential real estates in Addis Ababa - Yohannes, Selam; Dinku , Abebe (Zede Journal of Ethiopian Engineers and Architects, 2023)
Based on the current rate of growth (3.02%), the population of Ethiopia is expected to double in the next 30 years and cross 210 million by 2060 implying a higher demand in housing needs. It is learnt from the trend of housing development in Addis Ababa that reducing the housing backlogs has been a challenge to the Ethiopian city administration. Following the change of government in 1991, the Addis Ababa City Administration has considered private real estate sector to be one of the actors in housing development. In this article, housing provisions and affordability of private residential real estates in Addis Ababa are evaluated. The study includes: a brief overview of the affordability situation in residential real estates in selected countries, assessing the affordability of the private residential real estates in Addis Ababa and the standards of housing in relation to their costs are analyzed. It is found from the study that the private residential real estates are unaffordable to the average income holders of Addis Ababa residents. In addition, the standards of the selected private residential real estates lack excellence which is not consistent with the prices of the housing units. It is further recommended that a relevant housing policy should be introduced that accommodates low/middle income residents.